Constructivist сlassroom activities for biology learning in English - Zengin, О.; Kalkabekova, Zh.S.; Ganyukova, А.А. (KSU Publ., 2013)
There are many learning theories in the educational process of teaching-learning. Constructivism is unique because it focuses on developing the learners’ knowledge by constructing the world around them through experience, observation, documentation, analysis and reflection. This article contains the review of many classroom activities such as using concept maps, scenarios and songs, making up charts and schemes, case study which encourage thinking, understanding, exploration, problem solving, collaboration, analysis, observation and prediction.
Ағылшын тілінде биология сабағын оқытуда конструктивизм əдісін қолдану
Использование метода конструктивизма в преподавании биологии на английском языке
Keywords: constructivism; school education; biology teaching; classroom teaching; classroom activities; biology; education; learning; student; science